2014
DOI: 10.1007/s13277-014-2806-z
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of microRNA-21 as novel biomarker for diagnosing human cancers

Abstract: With cancer being a major cause of death worldwide, microRNAs (miRNAs) have been investigated as novel and non-invasive biomarkers for cancer diagnosis. Recently, microRNA-21 (miR-21) attracts much attention for its aberrant expression and has been widely studied in various cancers. However, the inconsistent results from studies make it hard to evaluate the diagnostic value of miR-21 in cancer diagnosis, which lead us to conduct this meta-analysis. We conducted a comprehensive literature search in the Medline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…In our meta-analysis, the pooled sensitivity and specificity were 0.72 and 0.80, which indicated that the diagnostic accuracy may not be high enough as expected. The results were consistent with the recently published studies by Li et al and Shen et al [27, 28]. However, compared with some traditional biomarkers, such as CEA, NSE (with sensitivities of 0.48 and 0.39), miR-21 still had higher diagnostic value in detecting breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…In our meta-analysis, the pooled sensitivity and specificity were 0.72 and 0.80, which indicated that the diagnostic accuracy may not be high enough as expected. The results were consistent with the recently published studies by Li et al and Shen et al [27, 28]. However, compared with some traditional biomarkers, such as CEA, NSE (with sensitivities of 0.48 and 0.39), miR-21 still had higher diagnostic value in detecting breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Other investigators reported high sensitivity and specificity of circulatory miR-21 for detecting other types of cancer, including gastric, esophageal, colorectal, pancreatic, lung, prostate, and ovarian cancer [33,34,[48][49][50][51][52][53][54][55]. Moreover, in a meta-analysis conducted on 73 studies with different cancers, the most identified cancer by miR-21 assay was BC, with 84 % specificity and 86 % sensitivity [56]. Taken together, these results held the point that miR-21 could serve as a potential broad-spectrum biomarker for cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies reported that plasma tumor markers with high concentrations are often found only when the disease is at an late stage (16)(17)(18)(19). Therefore, it is difficult to detect a lung tumor clinically at an early stage with plasma marker assays (20,21).…”
Section: Introductionmentioning
confidence: 99%